Harold bloom: la controversia s obre el canon (2001)
Laspregunt and lt;uporlaformacióndelcanon:cómosereali-Ulllsusselecciones,cómoseconvierteunteXtOencJási.co,quépoetasvanaperdurar,soncuestionesqueaparecenenlaobradeBloomdesdeelpnmermomento.Puededecinequelateoríadelainfluencia,comortorhcklrevisionismo,esalmismotiempoyaunateorladelcanon.Aúnantes,elperiodoinicialdeBloomcomocríticodelatradiciónrománticaes,enelsentidomásfuerte,unintenroporincidirenelcanondelapoeslainglesatalcomoJoencontróasuUegada.Elproblemadelcanones,pues,elmáspermanenteyelmasinquietantedelostemasalolargodetodalaobracríticadeHaroldBloom.